The Characterization of Felix Salinger as the Main Character in Morris Gleitzman’s Once - Suwastini, Ni Komang Arie; Pebriyanti, Ni Kadek Wuni; Wahyuni, Ni Luh Gede Eka; Susanthi, I Gusti Ayu Agung Dian (International Journal of Language and Literature, 2022)
The present study aimed to elaborate on the characterization of Felix Salinger, the main character in Morris Gleitzman’s Holocaust novel entitled Once. Through textual analysis, the study revealed that the novel portrays Felix Salinger as an eight-year-old Jewish boy who was religious, brave, caring, and creative. Felix Salinger's religious character involved strong tolerance toward Christianity and high respect for the higher powers in their various names. His bravery was shown when he had to accomplish many challenging tasks at the risk of his own life. Felix Salinger's caring characterizations were supported by his observant, attentive, and selfless characters. His creativity relied on his imagination to create solutions to various challenges he faced, including creating stories to entertain others as part of his survival. These findings imply that children can be very resilient in challenging situations.